Expanded ribosomal synthesis of non-standard cyclic backbones in vitro - Kanghun Lee; Hyeongwoo Park; Ravi Kumar Devarapalli; Dahye Im; Jongcheol Seo; Joongoo Lee (Nature Communications)
Abstract The ribosome polymerizes L-α-amino acids into polypeptides, catalyzing peptide bond formation through aminolysis. This process is facilitated by entropy trapping within its peptidyl transferase center (PTC). In this research, we harness this capability to synthesize polymers containing cyclic motifs in the backbone. We design 26 non-canonical monomers (ncMs) with two distinct substrates: dicarboxylic esters and hydrazinoesters, each containing bifunctional moieties that undergo ring-closing reactions through multiple aminolysis reactions. Using a cell-free system that enables the consecutive incorporation of these ncMs into a growing peptide, we discover that the ribosome can produce 5- and 6-membered cyclic backbones, which have never been reported. We also demonstrate that the formation of such cyclic backbones within the ribosome is tunable by altering the substituents of dicarboxylic esters. This discovery expands the range of non-standard backbones that can be synthesized by the ribosome and motivates future research towards expanding ribosome-mediated chemistries for biopolymer synthesis.